Relationship between ethical and discretionary dimensions of corporate social responsibility practices and job satisfaction of employees in a Malaysian public university - Chan, Tak Jie (2016)
This study aimed to examine the relationship between ethical and discretionary corporate social responsibility (CSR) dimensions with job satisfaction of employees in Universiti Putra Malaysia (UPM). The study utilised the revised pyramid of global CSR and performance model which proposed by Carroll’s by focused on the ethical and discretionary dimensions and collated with the best CSR practices which suggested by Mohd Hasan with the employees’ job satisfaction. In addition, the study also used Herzberg’s Motivation-Hygiene Theory to guide the research. Multistage sampling was employed in this study, whereby cluster sampling, simple random sampling, stratified sampling, and purposive sampling were used. A quantitative (survey) method was employed in this study, whereby questionnaires were distributed to 464 UPM staff (academic and non-academic), but with only 285 valid responses received. A set of self-administered questionnaire was used as the instrument for the data collection. The data were then analysed using descriptive statistics, Pearson’s Product-Moment Correlation test, and Multiple Regression test using the stepwise method through the Statistical Package of Social Science (SPSS) version 22.0. Based on the findings, the study revealed that the respondents have a high level of understanding of CSR practices. In addition, human rights, labour rights, environmental stewardship under ethical dimension and community driven, which categorised under discretionary dimension has positive and moderate relationships with job satisfaction. However, social reporting under the ethical dimension has a positive, but weak correlation with the job satisfaction. This had indicated that employees of UPM have positive views on UPM CSR initiatives and this will have a significant effect on their job satisfaction. Besides, multiple regression analysis showed that only labour rights of the ethical dimension and community driven from the discretionary dimension were the significant predicting factors for job satisfaction in UPM context. Hence, the findings suggest that in order to increase the employees’ job satisfaction, UPM should improve the labour rights practices and support community driven initiatives. Hence, UPM should emphasise on the equal chances of getting promotion based on meritocracy system as part of their ethical CSR practices. In addition, the management of UPM should also encourage their employees to actively participate in the community programmes and employ underprivileged groups as ways to foster the employees’ identification to build a bond with UPM as a socially responsible institution.